Exchange Depreciation and Economic Readjustment - Balogh, Thomas (The Review of Economics and Statistics, 1948)
THE postwar international economic and monetary settlement, especially Bretton Woods Final Act and original draft of International Trade Charter,' were based on conviction that national economic policies (including a policy of full employment) could always be harmonized with full adherence to an international system of unplanned market economies by alteration of foreign exchange rates. This is most clearly brought out by Lord Keynes' famous defense of Bretton Woods Agreement in House of Lords: . . we intend to prevent inflation at home, we will not accept deflation from dictate of influences from outside. other words, we abjure instruments of bank rate and credit contraction operating through increase of unemployment as a means of forcing our domestic economy into line with external factors; 2 and that In fact, plan introduces in this respect an epochmaking innovation in an international instrument, object of which is to lay down sound and orthodox principles. For instead of maintaining principle that internal value of a national currency should conform to a prescribed de jure external value, it provides that its external value should be altered if necessary so as to conform to whatever de facto internal value results from domestic policies, which in themselves shall be immune from criticism by Fund. Indeed, it is made duty of Fund to approve changes that will have this effect. That is why I say that these proposals are exact opposite of gold standard. I He furthermore contended that additional liquid reserves provided by international action would be sufficient to act as a buffer until equilibrating influence of alteration in exchange rates made its effects felt: the wheels of trade are to be oiled by what is, in effect, a great addition to world's stock of monetary reserves, distributed, moreover, in a reasonable way. 4 U. S. orthodox school assumed elasticities of demand for exports and imports to be great. 5 Indeed they were afraid that depreciation would be abused in order to obtain full employment by stimulating exports; and, accordingly, insisted that Fund should not permit lowering of exchange value of a currency before a long and large deficit in balance of payments occurred so as to be sure that disequilibrium was sufficiently to justify a change in value of currency. 6 There was no suspicion even that depreciation might not work or that it might generalize disequilibrium in system. difference between fundamental and temporary disequilibria in balances of payments was never defined, nor was there an attempt made to inquire into nature and causes of such disequilibria so as to be able to adapt remedial measures to specific 'U. S. Department of State. This was presumably an American product but it is characteristic of British delusions about future of Western Europe as an industrial center in a non-planned world that draft followed almost verbally proposals put forward-in a personal capacity by Professor J. E. Meade in Economic Basis of a Durable Peace (London, I940). On implications of opportunity to compete with U.S. on equal terms of Western Europe under rule of so-called non-discrimination, compare my essays, The Charter of ITO, Bulletin of Oxford University Institute of Statistics, Vol. 9, No. 3, and 'Britain and Geneva Tariff Agreements, Ibid., Vol. 9, No. 12. 2 Seymour E. Harris, Editor, New Economics (New York, I947), p. 3743Ibid., p. 376. This judgment was clearly based on excessive optimism with regard to relations of U. S. and Western Hemisphere in general to rest of world, an optimism brought out clearly in his famous forecast that The chances of dollar becoming dangerously scarce in course of next five or ten years are not very high (The Balance of Payments of U. S., Economic Journal, June I946, p. i85). 'Ibid., p. 372. 'G. Haberler, this REVIEW, XXVI (November I944), P. I9I. 6Ibid., p. i8i.